2020
DOI: 10.1371/journal.pone.0226378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of motif-based and whole-unique-sequence-based analyses of phage display library datasets generated by biopanning of anti-Borrelia burgdorferi immune sera

Abstract: Detection of protection-associated epitopes via reverse vaccinology is the first step for development of subunit vaccines against microbial pathogens. Mapping subunit vaccine targets requires high throughput methods, which would allow delineation of epitopes recognized by protective antibodies on a large scale. Phage displayed random peptide library coupled to Next Generation Sequencing (PDRPL/NGS) is the universal platform that enables high-yield identification of peptides that mimic epitopes (mimotopes). Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…In the current work, we report the isolation of a fast-propagating phage clone displaying the peptide WSLGYTG, which was enriched through screening of the commercial Ph.D. TM -7 phage display library against recombinant mouse CD4 protein. A literature search revealed that this peptide sequence has already been isolated in biopanning on two other targets, including human recombinant CD3 Ɛ protein (the epsilon chain of T-cell surface glycoprotein CD3) [ 15 ] and protective and non-protective anti- Borrelia burgdorferi sera of New Zealand White (NZW) rabbits [ 16 ]. However, the chance of obtaining a true binder on different targets in biopanning of a library containing billions of peptides is very unlikely, and the peptide might be a nonspecific ligand.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, we report the isolation of a fast-propagating phage clone displaying the peptide WSLGYTG, which was enriched through screening of the commercial Ph.D. TM -7 phage display library against recombinant mouse CD4 protein. A literature search revealed that this peptide sequence has already been isolated in biopanning on two other targets, including human recombinant CD3 Ɛ protein (the epsilon chain of T-cell surface glycoprotein CD3) [ 15 ] and protective and non-protective anti- Borrelia burgdorferi sera of New Zealand White (NZW) rabbits [ 16 ]. However, the chance of obtaining a true binder on different targets in biopanning of a library containing billions of peptides is very unlikely, and the peptide might be a nonspecific ligand.…”
Section: Discussionmentioning
confidence: 99%
“…A number of groups have looked at overlapping peptides presented on microarrays or in phage display libraries generated by tiling antigens or entire proteomes [35][36][37][38]. Bio-panning of phage or bacterial peptide display libraries coupled with next generation sequencing have provided broader binding profiles [39,40]. The advantage of tiling and panning approaches is that one is starting with known or suspected binding sequences, and thus the dataset is naturally rich in strong binding information.…”
Section: Introductionmentioning
confidence: 99%
“…A number of groups have looked at overlapping peptides presented on microarrays or in phage display libraries generated by tiling antigens or entire proteomes (22)(23)(24)(25)(26)(27). Panning of phage or bacterial peptide display libraries coupled with next generation sequencing have provided broader binding profiles (28,29). The advantage of tiling and panning approaches is that one is starting with known or suspected binding sequences, and thus the dataset is naturally rich in strong binding information.…”
Section: Introductionmentioning
confidence: 99%